1957
DOI: 10.1007/bf02637894
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes which take place in an edible oil during thermal oxidation

Abstract: Summary The thermal oxidation of corn oil proceeds in two steps, an initial period of 12 to 16 hrs., characterized by a decrease in iodine value and a rapid increase in carbonyl value, and a second phase in which a slower decrease in iodine value, a slight decrease in carbonyl value, and a rapid increase in viscosity occurred. Increasing the rate of aeration caused greater magnitude in changes but did not alter the over‐all two‐phase reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Yoon et al (1985) reported that the refractive index of rice bran oil and double fractioned palm olein increased almost linearly with the increase in heating time. In another study, Johnson and Kummerow (1957) investigated the chemical changes that take place in corn oil during thermal oxidation, and they reported that the corresponding refractive index of samples increased with thermal treatment duration at a constant temperature and with the increase of temperature at a constant treatment time.…”
Section: Physicochemical Properties Of the Control Mixed Oilmentioning
confidence: 99%
“…Yoon et al (1985) reported that the refractive index of rice bran oil and double fractioned palm olein increased almost linearly with the increase in heating time. In another study, Johnson and Kummerow (1957) investigated the chemical changes that take place in corn oil during thermal oxidation, and they reported that the corresponding refractive index of samples increased with thermal treatment duration at a constant temperature and with the increase of temperature at a constant treatment time.…”
Section: Physicochemical Properties Of the Control Mixed Oilmentioning
confidence: 99%
“…Such polymeric species rarely become larger than trimers or tetramers 12,23,42 , although an explicitly stated reason for this cannot be found in the open literature. One of the obvious results of polymer formation is an increase in the oil viscosity 18,43 . Under conditions where oxygen is available, fatty acid moieties are joined by both C-O-C linkages 3,23,42 and C-C linkages 42 .…”
Section: Secondary Products Of Oxidationmentioning
confidence: 99%
“…Once this isomerization has begun, a conjugated diene group from one fatty acid chain can react with a single olefin group from another fatty acid chain to form a cyclohexene ring 2,42 . This reaction between a conjugated di-olefin and a mono-olefin group is called the Diels Alder reaction, and it becomes important at temperatures of 250-300°C or more 8,18,23 . The products formed are called dimers.…”
Section: Thermal Polymerizationmentioning
confidence: 99%
See 2 more Smart Citations